Baseline Study on Knowledge, Attitude and Practice Assessments on Covid-19 Transmission and Preventive Actions Among Ecotourism Operators in Kuala Tahan and Kuala Gandah - Mat Puat, Nur Fasihah; Ahmad Azam, Shahidatulmunirah; Saad, Nurulwahida; Zainuddin, Norafiza; Kaderi, Mohd Arifin Bin (International Journal of Allied Health Sciences, 2024)
Background: The SARS-CoV-2 virus that caused COVID-19 led to a global pandemic with widespread impacts on economies, particularly the tourism sector. This study assesses COVID-19-related knowledge, attitudes, and practices (KAP) among ecotourism operators in Kuala Tahan and Kuala Gandah by exploring demographic factors influencing these variables. Methods: A cross-sectional design was employed, surveying 96 ecotourism operators using a structured and validated KAP questionnaire. The survey captured detailed demographic data and assessed COVID-19 knowledge, awareness, and preventive practices. Results: Overall, respondents demonstrated high knowledge of COVID-19 (mean score: 12.76, SD: 1.8) likely influenced by public health campaigns. Knowledge scores were significantly associated with gender and education background (p<0.05). Attitude and practice scores were also positively correlated with knowledge scores, showing mean scores of 4.2 (SD: 0.59) and 9.6 (SD: 0.91) respectively and there were weak to moderate positive correlations between KAP variables (p<0.01). Conclusion:These findings highlight the importance of targeted, demographic-specific education and the integration of technology to enhance health literacy and promote adherence to COVID-19 prevention measures in rural communities.